DAMPAK ACFTA TERHADAP PERDAGANGAN SEKTOR INDUSTRI DAN PERTANIAN INDONESIA (STUDI KOMPARATIF INDONESIA-CHINA DAN INDONESIA-VIETNAM) - Indah Kurniawati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2014)
The purpose of this study was to analyze the impact of ACFTA on the competitiveness of the agricultural and industrial sectors of Indonesia compared to China and Vietnam by using the RCA index and ISPs with the before-after approach. The data used are secondary data from UN Comtrade 1999-2003 (the period before ACFTA) and 2004-2011 (the period after ACFTA). The results of RCA index analysis indicate that the Indonesian industrial sector before and after the ACFTA has weak competitiveness in the China. In Vietnam, Indonesia has low competitiveness before ACFTA. However, after ACFTA, Indonesian industrial sector have strong competitiveness during 4 years (2006-2009). Before ACFTA, Indonesia tended to be an industrial exporter where the number of sub-sectors with positive ISP ranging between 57-73 percent. However, after ACFTA Indonesia became a net importer of industrial with ISP negative value below zero through one. Indonesia was an agricultural exporter with more positive ISP values of more than 50 percent before and after ACFTA. Based on the results, it is recommended that there should be such policies as reduction in trading cost, infrastructure improvement, bureaucratic reform to ease the licensing process, and development of manufacturing industries to gain added value. The policies are expected to boost economic activities in the industrial and agricultural sectors to increase competitiveness.Keywords: ASEAN-China Free Trade Agreement (ACFTA), revealed comparative advantage, trade specialization index